COMPARATIVE RESULTS OF ENDOSCOPIC VERSUS EXTERNAL DACRYOCYSTORHINOSTOMY FOR ACQUIRED NASO-LACRIMAL DUCT OBSTRUCTION - DR SHIV KUMAR RAGHUWANSHI; DR SAPNA RAGHUWANSHI M.S. (International Journal of Pharma and Bio Sciences, 2013)
Dacryocystorhinostomy (DCR) is the treatment of choice for acquired nasolacrimal duct obstruction, commonly caused by chronic dacryocystitis. Although external DCR is traditionally regarded as gold standard, endoscopic DCR is evolving as an equally effective alternative nowadays, with added advantage of preserving the lacrimal pump system and leaving no surgical scar. To compare the success rates of external and internal approaches of DCR for acquired nasolacrimal duct obstruction. A prospective, open lebel, non- randomized cohort study. Ninety consecutive patients with acquired nasolacrimal duct obstruction (62 females, 18 males, mean age 62.5 years) underwent DCR surgery. 60 patients were selected for endoscopic endonasal DCR, while the remaining 30 underwent DCR via external route. Success rate was defined by resolution of symptoms with patency of lacrimal drainage system immediately after surgery and at follow ups.The overall immediate success rate (achievement of patency by irrigation) was 90% (81/ 90 cases). Results were slightly better in endonasal DCR group (56 / 60; 93.33%) as compared to the external DCR (25/30; 83.33%), although statistically insignificant (p= 0.856). Long-term symptom relief and anatomical patency (6–12 months postoperatively) was retained in 53 (88.33%) patients of endonasal DCR and in 23 (76.66%) patients of external DCR. Out of 14 failed cases, anatomical obstruction at the fistula site was found in 9 (64.28%) case, the rest had functional failure. The success rate of DCR in our group of patients was high with an overall few complications. The results of endoscopic DCR were comparable to that of external DCR.